2019
DOI: 10.1007/s12028-019-00795-4
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Sleep Deprivation in the Neurological Intensive Care Unit: A Narrative Review

Abstract: Sleep is fundamental for everyday functioning, yet it is often negatively impacted in critically ill patients by the intensive care setting. With a focus on the neurological intensive care unit (NeuroICU), this narrative review summarizes methods of measuring sleep and addresses common causes of sleep disturbance in the hospital including environmental, pharmacological, and patient-related factors. The effects of sleep deprivation on the cardiovascular, pulmonary, immune, endocrine, and neuropsychological syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 210 publications
(204 reference statements)
1
29
0
Order By: Relevance
“…18,19 This has particular relevance for patients with strict blood pressure parameters such as patients with hypertensive and aneurysmal bleeds and chronic blood loss. 10,20-22 Increased sympathetic and decreased parasympathetic cardiovascular modulation was shown in normal humans with sleep deprivation. 18-20 Irwin et al, 23 had indicated elevation in level of C-reactive protein (CRP), an inflammatory marker shown to be an independent predictor of future myocardial infarction and stroke.…”
Section: Discussionmentioning
confidence: 99%
“…18,19 This has particular relevance for patients with strict blood pressure parameters such as patients with hypertensive and aneurysmal bleeds and chronic blood loss. 10,20-22 Increased sympathetic and decreased parasympathetic cardiovascular modulation was shown in normal humans with sleep deprivation. 18-20 Irwin et al, 23 had indicated elevation in level of C-reactive protein (CRP), an inflammatory marker shown to be an independent predictor of future myocardial infarction and stroke.…”
Section: Discussionmentioning
confidence: 99%
“… 35 Sleep disruption impacts several organ systems and has been found to be independently associated with delirium in the ICU. 36 , 37 Continuation of sleep disruption with hourly exams when no longer indicated may contribute to ICU delirium. Older age alone has been identified as a factor affecting sleep quality in the ICU.…”
Section: System-specific Considerations In Older Adultsmentioning
confidence: 99%
“…Circadian disruption may contribute to the development of acquired immunodeficiency that is observed to develop after several days of critical illness and leaves patients vulnerable to nosocomial infectious complications [37]. Drawing upon studies in other populations, circadian disruption likely impairs the function of many other systems, including endocrine-regulated processes, glycemic control and other metabolic pathways, autonomic and cardiac stability, lung function, renal clearance and liver function, the basis for which has been reviewed in details elsewhere [38]. In the remainder of this article, we will discuss the rationale for specific pharmacologic and environmental interventions that may attenuate sleep and circadian disruption in the ICU, with special attention to the neurologic population.…”
Section: Effect Of Circadian Rhythm and Sleep Disruption On Icu Outcomesmentioning
confidence: 99%